Renewable Energy from Osmosis: Design and Model Pressure Retarded Osmosis System - Liew, Zhen Shen (Universiti Teknologi PETRONAS, 2020)
Pressure Retarded Osmosis (PRO) shows notable potential as a renewable bioenergy alternative to counter water and energy shortage. To make PRO a reliable energy source, technological advances and in-depth research are required to improve its feasibility and cost efficiency. This research therefore aims to establish a mathematical model for simulating the power output of the laboratory scale PRO system. Consideration of concentrative polarization (ICP and ECP) effect on output power density is included as it is the key factor that impact the performance. The model is then used to simulate the output of four membrane samples, result shows an average accuracy of 99.55 %. Membrane 3 provides the maximum power density of 41.97 W/m2 among the membranes. It is then chosen and improved by deciding the optimal conditions for its operation. The first method of optimisation is by stabilising the effective membrane concentration. It can be achieved by retaining the draw solution concentration using automated dosing method.